REGIONAL DIFFERENTIATION OF INDUSTRY AND ECONOMIC DETERMINANTS IN NAMANGAN REGION (International Congress on Economics, Management and Business Studies, 2026)
In this study, the spatial location of industrial enterprises and the main factors affecting their development in the conditions of Namangan region were analyzed based on an econometric approach. The relationship between the change in the number of industrial enterprises in the districts and factors such as investment activity, labor resource potential, the level of development of transport and communication infrastructure, urbanization and market capacity was assessed using a multivariate regression model. The empirical results show that the volume of investments, the share of the economically active population and infrastructure provision have a statistically significant and positive effect on the territorial concentration of industry.
Keywords: industrial enterprises, econometric analysis, multivariate regression, territorial development, investment activity, infrastructure, labor resources, regional differences, industrial policy, Namangan region.